"Gateway to the gatekeepers", single point of access meetings: evaluating the client case referral procedure within an NHS Trust - Narayanasamy, Melanie Jay (2014)
This ESRC funded CASE studentship PhD project provides a comprehensive investigation into the referral allocation process within an NHS Trust’s adult mental health facilities, known as Single Point of Access (SPA) meetings. These meetings provide a multidisciplinary environment in which mental health practitioners consider client referrals in the form of letters from, primarily, General Practitioners (GPs) and direct them to appropriate services and interventions. Participants in these meetings can be seen as gatekeepers authorising access to other mental health services. The study was formally identified by NHS Research Ethics procedures as a service evaluation. From an academic perspective it is sociological research heavily informed by Glaserian Grounded Theory (GT) methodology. This approach has uncovered an internal Basic Social Process (BSP) underpinning SPA meetings. It has been named “Handling Role Boundaries”, and it describes how SPA meeting attendees endeavour to work together as they make crucial decisions about clients. Initial research plans included the collection and evaluation of quantitative data which would assess the relative validity of SPA meeting decisions. Unfortunately the quality of available data proved insufficient for this purpose. This provided brief insight into tensions between administrative systems and the real life mechanisms of SPA meetings. Overall, the unfulfilled evaluative purposes of the study provided an opportunity to focus more on clarifying the BSP underpinning SPA meetings. Also explored is how this BSP has wider implications for an understanding of how “mental health difficulties” are framed and provided for. The thesis concludes that Handling Role Boundaries is a highly innovative theory offering major contributions to understanding one social space of mental health professionals. Furthermore, it offers plentiful scope for further research and will be appropriate for many avenues of dissemination.